Sexual and reproductive health of quilombola women in Goiás - Lisbôa, Dalila Maria de ´Fátima; Pereira, Lucélia Luiz (Argumentum, 2023)
The article aims to discuss the sexual and reproductive health of quilombola women. The qualitative research was carried out at Quilombo Mesquita, Goiás, Brazil, and 10 semi-structured interviews were carried out with quilombola women between February and April 2022. As main results, it is highlighted that the interviewees positively evaluate prenatal care but point out limitations and/or lack of other sexual and reproductive health services such as reproductive planning, contraceptive methods, health education actions, basic health unit infrastructure, counter-reference services for childbirth. It is important to promote strategies to guarantee the sexual and reproductive rights of quilombola women, respecting diversity and seeking to combat the gender and racial discrimination, which was intensified in Brazil due to the contemporary conservative wave.Keywords: Women. Quilombolas. Racism. Sexual and reproductive health.